Factors associated with information credibility perceptions: a meta-analysis - Ou, Mengxue (2024)
Research on factors influencing information credibility judgment is increasing, whereas their findings are mixed. This study conducted a meta-analysis of 85 empirical studies, synthesizing the effects of 12 frequently examined source, content, channel, and receiver factors on information credibility perception. Results reveal that message quality, source credibility, and message fluency have large correlations with credibility perception, while other factors show small-to-medium correlations. Personal topic knowledge does not have a significant relationship with credibility perception. Gender composition, information channel, topic, and research method significantly moderate the aggregated relationships. The theoretical and practical implications are discussed.